Lope de Vega's Lo que pasa en una tarde : A Critical, Annotated Edition of the Autograph Manuscript - Vega, Lope de, 1562-1635 (Studies in the Romance languages and literatures, 2019)
This is the first critical analysis of this comedia de costumbres y de enredo, written in 1617 by the creator of the national Spanish theater. In his edition, Richard Picerno has retained the orthography of Lope's original autograph manuscript, in which modern capitalization, punctuation, and accentuation have been added.